Analytical modeling and ATLAS simulation for a homojunction LED in the mid-infrared spectral region - Sanjeev; Chakrabarti P. (My University, 2025)
A generic analytical model and the ATLAS simulation of a homojunction light emitting diode (LED) based on p+-InAs0. 91Sb0. 09/n0-InAs0. 91Sb0. 09/n+-InAs0. 91Sb0. 09 materials grown on lattice matched p+-GaSb substrate are presented. This LED is suitable for use as source in the optical absorption gas spectroscopy in the mid-infrared spectral region at 300 K. The various electro-optical properties of the homojunction LED are evaluated using analytical techniques and ATLAS device simulation software. The current-voltage characteristics of the structure are computed analytically and simulated, and the results are found to be in good agreement. The output power of the homojunction LED is estimated as a function of bias current under high carrier injection and compared with the reported experimental results. © 2009 Tianjin University of Technology and Springer Berlin Heidelberg.